A novel approach to the differential prognosis of early and late preeclampsia - A. N. Strizhakov; Е. V. Timokhina; S. M. Ibragimova; V. S. Belousova; Ya. O. Martirosyan (IRBIS LLC, 2018)
In the present review, a new approach to studying the pathogenesis and predicting the development of preeclampsia (PE) - namely, the determination of matrix metalloproteinases (MMPs) - is discussed. Currently, the major cause of PE is thought to be an incomplete remodeling of spiral arteries because of an insufficient number of invading cytotrophoblasts or the absence/inactivation of crucial lysing enzymes, i.e. matrix metalloproteinases. The role of MMP-1, MМP-2, MМP-3, MМP-7, MМP-9 in the placenta formation, the development of oxidative stress and endothelial dysfunction is described. We propose that in the future, the MMPs may be used for differentially predicting early and late PE.